1997
DOI: 10.1021/ic960969h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pseudohalide Ions on the Molecular Structure and Magnetic Properties of the Manganese(II)−Bipyrimidine−Pseudohalide System

Abstract: The compounds [Mn2(bpm)3(NCS)4] (1), [Mn(bpm)(NCO)2] (2), and [Mn2(bpm)(N3)4] (3) (where bpm= 2,2‘-bipyrimidine) have been synthesized and characterized. Compound 1 crystallizes in the triclinic P1̄ space group, with a = 9.122(1) Å, b = 9.229(1) Å, c = 11.710(2) Å, α = 74.89(1)°, β = 80.30(1)°, γ = 61.04(1)°, V = 831.7(2) Å3, Z = 2, R(F o) = 0.029, and wR(F o 2) = 0.078. Compound 2 crystallizes in the monoclinic C2/c space group, with a = 7.309(1) Å, b = 14.498(2) Å, c = 10.740(4) Å, β = 99.93(4)°, V = 1121.0(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…The ν(C=N) stretching frequency of the free ligand is observed at 1636 cm -1 . Complex 1·dmf records one strong band at 2070 cm -1 for the ν(CN) stretching of the terminally coordinated NCS - [38] ion, but the ν(CS) stretching frequency in the 700-825 cm -1 region could not be identified with certainty in the presence of strong absorptions by the organic ligand in this region. [39] Terminal coordination of azide groups to cobalt(II) ions in 2·CH 3 OH shows a very strong sharp band at 2050 cm -1 and a weak band at 1345 cm -1 for the ν as (N 3 -) and ν s (N 3 -) stretching vibrations, respectively.…”
Section: Infrared Spectroscopymentioning
confidence: 92%
“…The ν(C=N) stretching frequency of the free ligand is observed at 1636 cm -1 . Complex 1·dmf records one strong band at 2070 cm -1 for the ν(CN) stretching of the terminally coordinated NCS - [38] ion, but the ν(CS) stretching frequency in the 700-825 cm -1 region could not be identified with certainty in the presence of strong absorptions by the organic ligand in this region. [39] Terminal coordination of azide groups to cobalt(II) ions in 2·CH 3 OH shows a very strong sharp band at 2050 cm -1 and a weak band at 1345 cm -1 for the ν as (N 3 -) and ν s (N 3 -) stretching vibrations, respectively.…”
Section: Infrared Spectroscopymentioning
confidence: 92%
“…It has been reported that these networks may have electronic, magnetic, optical or catalytic applications (Batten & Robson, 1998;Dunbar & Heintz, 1997). For designing in®nite inorganic organic frameworks, we and others (Kim et al, 1999;Cortes et al, 1997;Demunno et al, 1997) (Wells, 1984 (Wells, 1984). The bond lengths and angles of the SCN and aniline ligands of (I) are unexceptional and similar to those reported in the literature (ZukermanSchpector et al, 1988).…”
Section: Commentmentioning
confidence: 99%
“…The complex cation can be described by a distorted octahedral environment around the central manganese(II) ion MnN 2 O 4 . Each manganese(II) ion is trans-coordinated by a pair of 3,4-dimethylpyridine ligands (Mn±N(1) 2.247(5) Mn±N(2) 2.289(5) A Ê ) in analogy to complexes containing N-(3,4-dimethylpyridine) and bipyrimidine [4,17]. The trans-angles deviate from linearity (N(1)±Mn±N(2) 175.7(2) ) as expected due to the geometrical constraints of the nitrate anion.…”
Section: Structurementioning
confidence: 99%